Discourses of development in the consulting room: Analysing family therapy with children. (August 2015) - Avdi, Evrinomy
This paper aims to highlight the potential contribution of the arguments developed in Burman's Deconstructing Developmental Psychology for exploring the implications of discourses around development for the practice of family therapy with children. Through the analysis of one brief systemic therapy with a stepfamily, formed following the mother's death, this paper examined how discourses from developmental psychology, including representations of children, father, mother, stepmother and family, are implicated in the construction of the problem and in the positioning of the participants. The diverse ways in which the family members made sense of their difficulties and the positions they assumed were shown to be intimately linked with culturally dominant representations of the biological nuclear family ideal and with representations of parents as responsible for their children's difficulties. The position of stepmother in particular was shown to be characterised by conflict and ambiguity, reflecting discourses that idealise motherhood and vilify stepmothers. Moreover, the children were found to be positioned as 'half-members' at several points in the conversation, whilst at other points they themselves resisted calls to a more equal positioning, particularly when disagreeing with the adults' talk. Family therapy, as an institutional practice, was shown to be intimately linked with developmental psychology accounts about childhood, family life and parenthood and Deconstructing Developmental Psychology was shown to provide valuable insights in researching family therapy with children. Based on the analysis, it is argued that paying attention to the social, ideological and cultural context in which family therapy takes place opens up novel ways of conceptualising and researching the process of therapy and allows the exploration of taken-for-granted assumptions about childhood, adulthood, parenthood and the family.